Storytime magic 400 fingerplays, flannelboards, and other activities - MacMillan, Kathy 1975-; Kirker, Christine (American Library Association, 2009)
Provides a generous sampling of art and craft ideas, songs, and action rhymes, designed to help veteran librarians refresh and enliven ongoing programs, while providing novice storytime planners what they need to get started.